(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
Increasing soil fertility is one of the most pressing problems. The reason is that fertile soils are extremely necessary for high productivity. Especially in the development of wheat, barley, rice and other high-need branches of today’s agriculture, it is becoming necessary to study the chemical composition of the soil and increase its fertility by chemical, biological, biotechnological methods. This article talks about a partial solution to such problems.